Anti quorum sensing and anti virulence activity of tannic acid and it's potential to breach resistance in Salmonella enterica Typhi / Paratyphi A clinical isolates. (January 2020) - Sivasankar, Chandran; Jha, Nisha Kumari; Ghosh, Ruchira; Shetty, Prathapkumar Halady
Abstract: Salmonella enterica Typhi and Paratyphi A are food borne pathogens causing typhoid, which is one of the most important food borne disease in the developing world. S. Typhi and S. Paratyphi A are of much concern as multi drug resistance has been on the rise. The current study is aimed to screen phytochemicals for anti quorum sensing (QS) activity against S. Typhi and S. Paratyphi A. Upon screening with swarming assay, tannic acid (TA) showed highest anti-QS activity with minimal concentration of 400μg/ml. The anti-QS activity of TA was confirmed with C. violaceum ATCC 12, 472. TA showed 38–43% and 35–50% of inhibition in cell surface hydrophobicity and EPS production respectively. Through FTIR analysis, it has been observed that EPS of treated cells has a considerable change in protein and peptide. TA has also exhibited drastic reduction in the surfactant production as high as 85–90%. Blood sensitivity and antibiotic sensitivity assay revealed that TA significantly sensitizes the S. Typhi and S . Paratyphi A cells to immune components in human blood and antibiotics. It has reduced the resistance of S. Typhi and S . Paratyphi A cells against amikacin, ampicillin, ciprofloxacin, azithromycin, chloramphenicol and gentamycin, thus revitalized the usage of these antibiotics against drug resistant S. Typhi and S . Paratyphi A infections. The consistency of anti-QS potential of TA was further evaluated and established with another eight clinical isolates of S. Typhi and S . Paratyphi A. Thus TA has been proved as a promising anti QS agent that can be developed as a therapeutic combination against S. Typhi and S . Paratyphi A. Highlights: Upon screening Tannic acid was found with anti-QS activity against S. Typhi and S. Paratyphi. TA has inhibited virulence factors such as CSH, EPS production, Surfactant production. TA has reduced the resistance of S. Typhi and S. Paratyphi against human blood and antibiotics.